2020
DOI: 10.1017/s1755773920000259
|View full text |Cite
|
Sign up to set email alerts
|

Hurricane or fresh breeze? Disentangling the populist effect on the quality of democracy

Abstract: Are populist actors more like a hurricane that risks undermining democracy? Or do they aim for a different type of democracy, which strengthens popular control? This article offers one of the most extensive, systematic analyses on the impact of populism on multiple functions of the Quality of Democracy. Going beyond the view of ‘high-’ or ‘low-quality’ democracies, we emphasize that the Quality of Democracy is related to multiple dimensions or ‘functions of democracy’, characterized by important trade-offs. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…They may also provide an important voice for ordinary people in times of economic and political crisis (Stavrakakis & Katsambekis 2014). The data suggest that populist parties do boost participation and improve vertical representation, especially if they contest elections but remain in the opposition and if they belong to the political left wing ( Juon & Bochsler 2020). Left-wing populist parties with an inclusive conception of the people may also have a positive impact on minority rights (Huber & Schimpf 2017).…”
Section: Populism and The Quality Of Democracy: Vertical Representation Yes; Horizontal Checks Nomentioning
confidence: 99%
See 1 more Smart Citation
“…They may also provide an important voice for ordinary people in times of economic and political crisis (Stavrakakis & Katsambekis 2014). The data suggest that populist parties do boost participation and improve vertical representation, especially if they contest elections but remain in the opposition and if they belong to the political left wing ( Juon & Bochsler 2020). Left-wing populist parties with an inclusive conception of the people may also have a positive impact on minority rights (Huber & Schimpf 2017).…”
Section: Populism and The Quality Of Democracy: Vertical Representation Yes; Horizontal Checks Nomentioning
confidence: 99%
“…While parties that use populist appeals are not all led by aspiring authoritarians (Bonikowski 2017), on the global level the data suggest a propensity for undermining democratic institutions. Scholars argue that government by populists across the ideological spectrum is associated with weakening institutional safeguards such as the rule of law and state transparency ( Juon & Bochsler 2020; see also Haggard & Kaufman 2021, Huber & Schimpf 2017. Populist parties across the board question the competence and the integrity of mainstream parties and conceptualize the elite as a separate "caste" whose interests are at odds with those of the people (Ivaldi et al 2017).…”
Section: Populism and The Quality Of Democracy: Vertical Representation Yes; Horizontal Checks Nomentioning
confidence: 99%
“…Empirical research on the country-and party-level by and large supports these concerns. Studies show that populist parties and leaders have eroded checks and constraints on the executive (Ruth 2018;Houle and Kenny 2018;Huber and Schimpf 2017;Juon and Bochsler 2020), have hampered media freedom (Juon and Bochsler 2020; Kenny 2020), and have attacked minority rights (Huber and Schimpf 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This radical majoritarian vision of representation also clashes with norms of political pluralism in debate and institutions. Empirical research on the relationship between the presence of populist parties and the quality of democracy by and large confirms the detrimental effect of populism on democracy (Ruth 2018;Houle and Kenny 2018;Huber and Schimpf 2017;Juon and Bochsler 2020).…”
Section: Introductionmentioning
confidence: 88%
“…Similarly, mainstream media (i.e., in their role as Fourth Estate) have faced increased pressure from populists (Kenny 2020). Thus, strong evidence has suggested that populist actors undermine the balance between the political institutions (Mudde and Rovira Kaltwasser 2012, Huber and Schimpf 2017, Juon and Bochsler 2020. Scholarly evidence suggests that similar mechanisms hold on the individual level (Akkerman et al 2014, Heinisch and Wegscheider 2020, Plescia and Eberl 2021.…”
Section: Populism Institutional Trust and Climate Scepticismmentioning
confidence: 99%